Does current management of storm water runoff adequately protect water resources in developing catchments? - Hur, J; Schlautman, M.A; Templeton, S.R; Karanfil, T; Post, C.J; Smink, J.A; Song, H; Goddard, M.A; Klaine, S.J; Hayes, J.C (Journal of soil and water conservation, 2008)
The effectiveness of best management practices (BMPs) at preventing erosion and controlling storm water and sediment runoff in developing catchments in the Reedy River (South Carolina) watershed was evaluated from 2004 to 2005. Catchment-normalized storm water runoff and event mean concentrations and cumulative mass loads of selected pollutants were compared among four catchments exhibiting similar rainfall, soil, and geographic characteristics but undergoing varying degrees of development. Despite the implementation of BMPs, streams below catchments undergoing active development exhibited patterns characteristic of urbanized watersheds, namely, storm hydrographs characterized by steep rising and descending limbs due to accelerated storm water runoff. In contrast with the developing catchments, streams below relatively undisturbed catchments exhibited more gradual rising and descending limbs on their hydrographs, presumably due to enhanced infiltration and interflow and less direct surface runoff. A comparison of surface runoff depths and runoff ratios confirmed more direct surface runoff was generated from rainfall in the developing catchments versus the undisturbed catchments despite the use of BMPs. In addition, area-normalized maximum stream discharges during storm events were generally higher for the developing versus undisturbed catchments. Similarly, mean concentrations and mass loads of total suspended solids were consistently higher for the developing versus undisturbed catchments. In many cases, mean concentrations for total suspended solids and other selected pollutants in storm water runoff from the developing catchments exceeded recognized water quality criteria. Taken together, the quantity and quality of storm water runoff from the developing catchments indicate that the overall protective goals of erosion prevention and sediment control regulations are not being met. Possible explanations for this include BMPs that have not been properly designed or located, are not the correct type, are insufficiently numerous, and/or have not been adequately maintained to control the increased surface runoff and/or soil erosion due to land disturbance. Alternatively, the failure may reflect shortcomings in the regulations themselves.